ANALISIS EKSEGETIS MENGENAI DISIPLIN ROHANI DALAM RENCANA ALLAH MENURUT IBRANI 12:1-17 - Dani Istiono (SAGACITY : Journal of Theology and Christian Education, 2021)
Spiritual discipline consists of two things, namely the discipline of commitment that is planned by humans to train themselves and the divine discipline that is planned by God for the good of believers. Divine Discipline is a manifestation of God's upbringing for believers or disciples of Christ, a form of discipline to express His love and justice. Discipline to express His love means that God wills that everyone who has received grace does not distance himself from that love or is known as apostasy. Then the discipline to declare His justice aims to educate every believer to keep their faith until the end of their lives and help believers to maintain the grace of God that He has provided.